Maternal and paternal anxiety levels through primary lip surgery - ABUHAN, ECE; YILMAZ, HANİFE NURAY (ELSEVIER, 2020)
Aim: The aim of this study was to evaluate the anxiety levels of the parents of infants with cleft lip and palate (CLP) before and after primary lip surgery. Materials and method: Forty mothers (mean ages: 31.9 +/- 6.16 years) and 40 fathers (mean ages: 34.6 +/- 5.91 years) of infants with CLP were included in this study. They were asked to answer the Amsterdam Preoperative Anxiety and Information Scale (APAIS) and Spielberger's State-Trait Anxiety Inventory (STAI) just 1 h before the primary lip surgery (T0) and 1 month after (T1) surgery. Student t-test and Mann-Whitney U test were used for inter-group comparison, the paired-sample t was used for the intragroup comparisons (p < 0.05). Results: There were no statistically significant differences for the comparisons of state (STAI-S) and trait (STAI-T) anxiety or APAIS scores between the parents. While state anxiety scores of the mothers increased significantly post-surgically, APAIS scores showed significant decreases in both parents (p < 0.05). APAIS scores of the fathers with bilateral CLP infants were significantly higher (p < 0.05) than the fathers of unilateral ones. The parents with local anesthesia experience showed significantly lower APAIS scores (p < 0.05). A negative correlation was present between maternal age and STAI-T, whereas a positive correlation was present between paternal age and the anxiety. Conclusions: The anxiety levels of the parents were similar. Parents asked for more information about the anesthesia than the surgery, therefore communication with the anesthesiologist in the preoperative period is important. Routine assessment of parents' stress and psychosocial support should be provided by the cleft team. (C) 2020 Elsevier Masson SAS. All rights reserved.
Keywords: Anxiety; APAIS; Cleft lip and palate; STAI; CLEFT-LIP; AND/OR PALATE; PARENTS; INFORMATION; CHILD; SATISFACTION